MANAJEMEN SEKOLAH ISLAM TERPADU DALAM PEMBENTUKAN KARAKTER BANGSA YANG PANCASILAIS DI SDIT MUHAMMADIYAH GUNUNG TERANG DAN SDIT PERMATA BUNDA III SUKABUMI BANDAR LAMPUNG - Tuala, Riyuzen Praja (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2018)
Abstract This study aims to determine the development of quality management-based teaching staff at SDIT Muhammadiyah Gunung Terang and SDIT Permata Bunda III Sukabumi Bandar Lampung. The focus of the problem in this study was on the management aspects of teacher quality coaching. This study used a qualitative approach with a case study design. Data is collected through: 1. Interviews with Principals, Foundation Managers and Teachers. 2. Data is also collected by examining and collecting relevant documents. 3. Make direct observations in both schools. To test the validity of the data used credibility, transferability, dependability, and confirmation. The collected data were analyzed by data analysis techniques including: data reduction (data reduction), presentation of data (display), verification / conclusion (conclusionsdrowing / verifiying). The results of the study showed that the two schools had implemented a modern teacher development pattern through the implementation of three-step management, namely planning, implementation and evaluation. The orientation of teacher development is directed at two main things, namely the achievement of high academic competencies (pedagogic, social, personal and professional), spiritual competencies that are